(untitled) (Journal of the College of Basic Education, 2022)
The educational process seeks to achieve educational and educational goals, the most important of which is the students’ access to mastering most of the cognitive and technical skills, and our current study (the impact of the Keeler plan for technical learning in acquiring handicraft skills for middle school students in art education) constitutes an important contribution to enriching the knowledge and skills aspect of art students in general. And for middle school students - our current research community - in particular, and accordingly the researcher organized her scientific material with this modest study by formulating the research problem and its importance The research aims to identify the effect of Keeler’s mastery of learning plan in acquiring handicraft skills for middle school students in art education The first chapter represents (the general framework of the research) and organizes the research problem and the importance and limits of the research represented by the students of the second intermediate grade who study the subject of art education, which includes handicraft skills and define the terms contained in the title of the research. As for the second chapter, it includes the theoretical framework representing the constructivist theory, Keeler’s plan for technical learning, skill and handicrafts, and previous studies and their discussion. As for the third chapter, it includes a presentation of the research methodology and procedures Appropriate experimental design, defining the research community, selecting the sample and its homogeneity, equivalence procedures between the experimental and control groups, controlling the variables and building the two research tools, leading to the application of the experiment, and the appropriate statistical methods. Manual for middle school students, and then conclusions, recommendations and sources.